Electrolyte for improving interface stability of four-electron aqueous zinc-iodine battery and aqueous zinc-iodine battery

By using an electrolyte containing N,N-dihydroxyethylglycine, zinc sulfate and specific additives in zinc-iodine batteries, the problems of interface instability and side reactions in zinc-iodine batteries are solved, achieving higher cycle stability and Electrochemical properties.

CN119340508APending Publication Date: 2025-01-21ANHUI UNIV

Patent Information

Application Number
CN202411859564.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The problems of unstable interface of zinc-iodine batteries, narrow electrochemical potential windows and side reactions have limited the widespread application of zinc-iodine batteries.

Method used

A electrolyte, which contains n, n-dihydroxyl ethyl, zinc sulfate, additives (such as methyl trimethylsonium chloride, beet-hydrochloride, hydrolytic bromate hydrochloride) and water Through the synergistic effect of these ingredients, optimize the sedimentary dynamics of the zinc negative surface, inhibit the growth of Zhi crystal, form a stable protective film, regulate the solventive environment, and reduce side reactions.

Benefits of technology

It significantly enhances the stability of the interface of the zinc iodine battery, improves the cycle stability and electrochemical properties, extends the service life of the battery, and improves the safety and reliability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340508A_ABST
    Figure CN119340508A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery, and belongs to the technical field of zinc-iodine battery electrolyte additives, the electrolyte comprises N, N-dihydroxyethyl glycine, zinc sulfate, an additive and water; in the electrolyte, the concentration of the N, N-dihydroxyethyl glycine is 0.5 + / -0.2 mol / L; the molar ratio of the additive to the zinc sulfate is 1: 3; the additive comprises any one of methyl triethyl ammonium chloride, betaine hydrochloride and triethylamine hydrobromide. The electrolyte can enhance the interface stability of the electrode electrolyte, improve the cycling stability and electrochemical performance of the aqueous zinc-iodine battery, inhibit side reactions, and improve the safety and reliability of the battery. The invention also provides a high-capacity aqueous zinc-iodine battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zinc-iodine battery electrolyte additives, and particularly relates to an electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery and an aqueous zinc-iodine battery. Background Art

[0002] At present, renewable energy such as wind power and solar energy has become the best choice for sustainable development. The unique advantages of renewable energy have driven a surge in demand for battery energy storage systems. In the process of transitioning to renewable energy, large-scale energy storage infrastructure is the current key challenge. In the energy storage system, lithium-ion batteries (LIBs) have good practical value, but with the continuous development of commercialization, the high cost, poor safety and thermal decomposition of LIBs have forced people to seek alternative energy systems. Among various battery systems, aqueous zinc-ion batteries (AZIBs) have attracted widespread attention due to their excellent environmental performance, good safety and rich content. In particular, the high specific capacity, faster redox kinetics and good reversibility of Zn-I2 batteries can also be well adapted to large-scale energy storage in the power grid.

[0003] At present, the interface of zinc-iodine batteries faces multiple challenges, including the short-circuit risk caused by the growth of zinc dendrites on the zinc negative electrode, the consumption of active zinc caused by hydrogen evolution reaction, and the accumulation of negative electrode corrosion products, which cause surface passivation and increase of internal resistance. At the same time, during the battery cycle, the I2 positive electrode will react with its discharge product I - The ions are complexed to form I3, which has high solubility. - Ions, these polyiodine ions will dissolve into the electrolyte and migrate to the zinc negative electrode side with the electrolyte, accelerating the battery self-discharge and zinc negative electrode interface corrosion rate by oxidizing the metal zinc negative electrode. This process not only consumes active zinc, but also aggravates the degradation of the battery. These shortcomings limit the widespread application of zinc-iodine batteries. Summary of the invention

[0004] In order to solve the problems of unstable electrode-electrolyte interface, narrow electrochemical potential window and side reactions in existing zinc-iodine batteries, the present invention provides an electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery. The electrolyte can enhance the electrode-electrolyte interface stability, improve the cycle stability and electrochemical performance of the aqueous zinc-iodine battery, inhibit side reactions, and improve the safety and reliability of the battery.

[0005] The invention also provides a high-capacity aqueous zinc-iodine battery.

[0006] The present invention is achieved through the following technical solutions: The present invention provides an electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery, wherein the electrolyte comprises N,N-dihydroxyethylglycine, zinc sulfate, an additive and water; In the electrolyte, the concentration of N,N-dihydroxyethylglycine is 0.5±0.2 mol / L; The molar ratio of the additive to the zinc sulfate is 1:3; The additive includes any one of methyltriethylammonium chloride, betaine hydrochloride and triethylamine hydrobromide.

[0007] Furthermore, in the electrolyte, the concentration of zinc sulfate is 2±0.5 mol / L.

[0008] Preferably, in the electrolyte, the concentration of zinc sulfate is 2 mol / L.

[0009] Preferably, in the electrolyte, the concentration of N,N-dihydroxyethylglycine is 0.5 mol / L.

[0010] Based on the same inventive concept, the present invention provides a method for preparing an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery, the preparation method comprising: N,N-dihydroxyethylglycine, additives and zinc sulfate are dissolved in water and then subjected to ultrasonic treatment to obtain an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery.

[0011] Based on the same inventive concept, the present invention provides an application of an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery in the preparation of an aqueous zinc-iodine battery.

[0012] Based on the same inventive concept, the present invention provides an aqueous zinc-iodine battery, wherein the aqueous zinc-iodine battery contains the above-mentioned electrolyte for improving the interface stability of the four-electron aqueous zinc-iodine battery.

[0013] Based on the same inventive concept, the present invention provides a high-capacity aqueous zinc-iodine battery, which uses an iodine composite material as a positive electrode, metal zinc as a negative electrode, a glass fiber membrane as a separator, and the above-mentioned electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery as an electrolyte.

[0014] Furthermore, the positive electrode is prepared by the following method: Conductive carbon and polyvinylidene fluoride (PVDF) are co-dispersed in NMP (N-methyl-2-pyrrolidone) to obtain a slurry; Dissolving potassium iodide and elemental iodine in water to obtain an iodine source solution; The slurry is coated on a current collector, and after vacuum drying, the iodine source solution is added dropwise to obtain a positive electrode.

[0015] Preferably, the mass ratio of the conductive carbon to the polyvinylidene fluoride is 8:2; The molar ratio of the potassium iodide to the iodine element is 10:1, and the concentration of the potassium iodide in the iodine source solution is 1 mol / L; The mass ratio of the conductive carbon to the iodine element is 1:1.2.

[0016] Based on the same inventive concept, the present invention also provides a zinc-zinc symmetrical battery, which uses zinc foil as the positive and negative electrodes of the battery, a glass fiber membrane as a separator, and the above-mentioned electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery as an electrolyte.

[0017] Based on the same inventive concept, the present invention also provides a zinc-copper asymmetric battery, which uses zinc foil as a negative electrode, copper foil as a positive electrode, a glass fiber membrane as a separator, and the above-mentioned electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery as an electrolyte.

[0018] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages: 1. The present invention discloses an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery. The electrolyte is added with N,N-dihydroxyethylglycine on the basis of zinc sulfate and water. With its unique molecular structure and rich functional groups, the electrolyte optimizes the deposition kinetics on the surface of the zinc negative electrode, effectively inhibits the growth of dendrites, and significantly enhances the interfacial stability. It should be noted that the electrolyte is additionally added with one of methyltriethylammonium chloride, betaine hydrochloride and triethylamine hydrobromide, wherein the triethylamine hydrobromide can effectively improve the theoretical capacity while improving the working potential of the battery, thus providing a new path for the application of aqueous zinc-iodine batteries in the field of large-scale energy storage, showing good practical application potential, and providing an experimental basis for the design and development of electrolytes for batteries with long cycle life.

[0019] 2. The present invention discloses an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery. Zinc sulfate in the electrolyte serves as a zinc source to provide zinc ions required for a battery reaction. Any one of methyltriethylammonium chloride, betaine hydrochloride, and triethylamine hydrobromide can form a stable and dense protective film at the interface between the electrolyte and the electrode, effectively reducing direct corrosion of the electrolyte on the electrode and improving the cycle stability of the battery. N,N-dihydroxyethylglycine contains a hydroxyl group, a carboxyl group, and a nitrogen atom rich in lone pair electrons. N,N-dihydroxyethylglycine promotes uniform deposition of zinc ions on the electrode surface and inhibits the growth of zinc dendrites by regulating the solvation environment of zinc ions. The rich functional groups help to regulate the pH of the solution and reduce the generation of byproducts (Zn4SO4(OH)6·xH2O). The problem of side reactions caused by the unstable interface of a traditional aqueous zinc-iodine battery and poor battery cycle performance is solved, and the safety and reliability of the battery are improved.

[0020] 3. The present invention discloses an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery. The halogen atoms provided by methyltriethylammonium chloride, betaine hydrochloride and triethylamine hydrobromide in the electrolyte can form a four-electron reaction mechanism. N,N-dihydroxyethylglycine contains abundant lone pairs of electrons, which are helpful for adsorbing intermediate reaction products of iodine, inhibiting the "shuttle effect" of iodine, maintaining the stability of the positive electrode material, and promoting the zinc-iodine battery to have a higher theoretical capacity while improving the working potential, which is helpful for improving the practical value of the zinc-iodine battery in a large-scale energy storage system. The additive (methyltriethylammonium chloride) The abundant functional groups in ethylammonium chloride, betaine hydrochloride, and triethylamine hydrobromide can form hydrogen bonds with water, improve the hydrogen bond network in the solution, reduce the contact between solvated zinc ions and active water, and inhibit hydrogen evolution in the system. At the same time, the three organic additives are rich in nitrogen elements, which provide active sites for zinc ion coordination and can be adsorbed on the surface of the zinc negative electrode. The dissolution process and zinc deposition kinetics are also optimized. The morphology of zinc deposition is denser and smoother, which effectively solves the irregular nucleation and diffusion process on the zinc surface, inhibits the enrichment of zinc at the tip, and weakens the occurrence of the "tip effect".

[0021] 4. The present invention discloses an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery. The N,N-dihydroxyethylglycine with pH buffering capacity in the electrolyte can inhibit the occurrence of side reactions. The concentration of the N,N-dihydroxyethylglycine is 0.5 mol / L, which promotes the uniform deposition of zinc ions on the electrode surface. The methyltriethylammonium chloride, betaine hydrochloride and ethylamine hydrobromide added in a specific proportion make the four-electron zinc-iodine battery have high stability and high capacity. The synergistic effect of the additive triethylamine hydrobromide, N,N-dihydroxyethylglycine and zinc sulfate can significantly improve the interfacial stability and cycle performance of the aqueous zinc-iodine battery, and support the four-electron zinc-iodine battery reaction. The electrolyte is applied to the aqueous zinc-iodine battery. The obtained battery exhibits excellent cycle stability and electrochemical performance during the cyclic charge and discharge process, thereby extending the service life of the battery.

[0022] 5. The present invention discloses an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery. The electrolyte has good solubility and dispersibility, ensuring uniform distribution of various components during the operation of the battery. The preparation method is simple, low-cost, and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0024] Figure 1This is a rate performance diagram of a symmetrical battery of methyltriethylammonium chloride electrolyte obtained in Example 1 of the present invention; Figure 2 This is a rate performance diagram of a zinc-iodine full-cell of a methyltriethylammonium chloride electrolyte obtained in Example 1 of the present invention; Figure 3 This is the charge and discharge curve of the methyltriethylammonium chloride electrolyte zinc iodine full battery obtained in Example 1 of the present invention; Figure 4 This is a rate performance diagram of a symmetrical battery of betaine hydrochloride electrolyte obtained in Example 2 of the present invention; Figure 5 This is a rate performance diagram of a betaine hydrochloride electrolyte zinc-iodine full battery obtained in Example 2 of the present invention; Figure 6 This is the charge and discharge curve of the betaine hydrochloride electrolyte zinc iodine full battery obtained in Example 2 of the present invention; Figure 7 This is a rate performance diagram of a symmetrical battery of triethylamine hydrobromide electrolyte obtained in Example 3 of the present invention; Figure 8 This is a rate performance diagram of a triethylamine hydrobromide electrolyte zinc iodine full cell obtained in Example 3 of the present invention; Fig. 9 This is the charge and discharge curve of the triethylamine hydrobromide electrolyte zinc iodine full battery obtained in Example 3 of the present invention.

[0025] Fig.10 This is the charge and discharge curve of the zinc-iodine full battery assembled with the electrolyte obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.

[0027] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.

[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0029] The technical principle of the present invention is as follows: The present invention provides an electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery, wherein the electrolyte comprises N,N-dihydroxyethylglycine, zinc sulfate, an additive and water; In the electrolyte, the concentration of N,N-dihydroxyethylglycine is 0.5±0.2 mol / L; The molar ratio of the additive to the zinc sulfate is 1:3; The additive includes any one of methyltriethylammonium chloride, betaine hydrochloride and triethylamine hydrobromide.

[0030] In the present invention, the concentration of N,N-dihydroxyethylglycine is 0.5±0.2 mol / L, which has the advantage of being able to effectively adjust pH, improve the hydrogen bond network and solvation structure in the solution, and inhibit side reactions. When the concentration is too low, good effects cannot be achieved, and when the concentration is too high, the viscosity is too high and the performance is attenuated.

[0031] In the present invention, the molar ratio of the additive to zinc sulfate is 1:3, and a high-capacity zinc-iodine battery can be obtained while controlling the concentration of zinc ions appropriately. If the molar ratio is too high, halogen atoms will corrode the zinc negative electrode, while if the molar ratio is too low, the four-electron reaction will be incompletely excited.

[0032] Based on the same inventive concept, the present invention provides a high-capacity aqueous zinc-iodine battery, wherein the aqueous zinc-iodine battery uses an iodine composite material as a positive electrode, metallic zinc as a negative electrode, and the above-mentioned electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery as an electrolyte.

[0033] Furthermore, the positive electrode is prepared by the following method: Conductive carbon and polyvinylidene fluoride (PVDF) are co-dispersed in NMP to obtain a slurry; Dissolving potassium iodide and elemental iodine in water to obtain an iodine source solution; The slurry is coated on a current collector, and after vacuum drying, the iodine source solution is added dropwise to obtain a positive electrode.

[0034] Preferably, the mass ratio of the conductive carbon to the polyvinylidene fluoride is 8:2; The molar ratio of the potassium iodide to the iodine element is 10:1, and the concentration of the potassium iodide in the iodine source solution is 1 mol / L; The mass ratio of the conductive carbon to the iodine element is 1:1.2.

[0035] In the present invention, the mass ratio of conductive carbon to polyvinylidene fluoride is 8:2, which has the advantage of obtaining a stable positive electrode material with good full battery cycle performance. The molar ratio of potassium iodide to iodine is 10:1, which has the advantage of providing a sufficient iodine source.

[0036] The electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery and the aqueous zinc-iodine battery of the present invention will be described in detail below in conjunction with embodiments and experimental data.

[0037] In this series of experimental studies, we used the Xinwei battery test system to conduct a detailed evaluation of battery performance. In particular, we designed a series of batteries in which zinc foil served as both the positive and negative electrodes, and the glass fiber membrane served as the key diaphragm component. In order to explore the effects of different four-electron electrolytes on battery performance, we innovatively used a 2M ZnSO4 solution containing methyltriethylammonium chloride, betaine hydrochloride, and triethylamine hydrobromide as the electrolyte. This electrolyte system is designed to promote the four-electron transfer process, thereby optimizing battery performance.

[0038] In the embodiment, we constructed a battery structure with zinc foil as the negative electrode and copper foil as the positive electrode, and also used a glass fiber membrane as a separator, and continued to use the above-mentioned innovative electrolyte system. Under room temperature conditions, we assembled a 2032-type zinc-copper button battery to evaluate its coulomb efficiency and retention rate. We used a ZnSO4 mixed solution containing a specific proportion of methyltriethylammonium chloride, betaine hydrochloride and triethylamine hydrobromide as an electrolyte. The electrolyte system is designed to promote the transfer process of four electrons. Under room temperature conditions, we assembled a 2032-type button battery and set a test voltage range of 0.6 V to 1.8 V. It should be emphasized that since the properties and interactions of chemical substances may vary depending on specific conditions, in practical applications, the formula and proportion of the electrolyte may need to be fine-tuned according to experimental results to achieve the best four-electron transfer process and battery performance.

[0039] Unless otherwise specified, conventional methods are used in the present invention.

[0040] Example 1

[0041] Step 1: Take 5 ml of deionized water and add it to a clean beaker. Weigh 0.815 g of N,N-dihydroxyethylglycine, 1.015 g of methyltriethylammonium chloride and 3.229 g of zinc sulfate, add them to the water and stir until it becomes clear.

[0042] Step 2: Add deionized water to the solution in step 1 to make it 10 ml and sonicate until it is homogeneous.

[0043] Step 3: Assemble the zinc-zinc symmetrical battery with the prepared electrolyte.

[0044] Step 4: Prepare a composite electrode material of conductive carbon Ketjen black and PVDF, accurately control the mass ratio to 8:2, evenly disperse it in NMP, and coat it on a carbon cloth current collector. After vacuum drying at 80°C for 8 hours, add 10 μL of a mixed solution of potassium iodide and iodine to obtain a positive electrode material (wherein the mass of Ketjen black is 16 mg, the mass of NMP is 90 μL, and the concentration of KI in the mixed solution is 1 M, and the concentration of iodine is 0.1 M).

[0045] Step 5: Assemble the zinc-iodine full battery using the prepared positive electrode material.

[0046] Example 2

[0047] Step 1: Take 5 ml of deionized water and add it to a clean beaker. Weigh 0.815 g of N,N-dihydroxyethylglycine, 1.025 g of betaine hydrochloride and 3.229 g of zinc sulfate, add them to the water and stir until it becomes clear.

[0048] Step 2: Add deionized water to the solution in step 1 to make it 10 ml and sonicate until it is homogeneous.

[0049] Step 3: Assemble the zinc-zinc symmetrical battery with the prepared electrolyte.

[0050] Step 4: Prepare a composite electrode material of Ketjen black and PVDF, and precisely control the mass ratio to be 8:2. Evenly disperse in NMP and apply to a carbon cloth current collector, and after vacuum drying at 80°C for 8 hours, drop 10 microliters of a mixed solution of potassium iodide and iodine to obtain a positive electrode material (the amounts of each raw material of the positive electrode material are the same as in Example 1).

[0051] Step 5: Assemble the zinc-iodine full battery using the prepared positive electrode material.

[0052] Example 3

[0053] Step 1: Take 5 ml of deionized water and add it to a clean beaker. Weigh 0.815 g of N,N-dihydroxyethylglycine, 1.20 g of triethylamine hydrobromide and 3.229 g of zinc sulfate, add them to the water and stir until it becomes clear.

[0054] Step 2: Add deionized water to the solution in step 1 to make it 10 ml and sonicate until it is homogeneous.

[0055] Step 3: Assemble the zinc-zinc symmetrical battery with the prepared electrolyte.

[0056] Step 4: Prepare a composite electrode material of Ketjen black and PVDF, and precisely control the mass ratio to be 8:2. Evenly disperse in NMP and apply to a carbon cloth current collector, and after vacuum drying at 80°C for 8 hours, drop 10 microliters of a mixed solution of potassium iodide and iodine to obtain a positive electrode material (the amounts of each raw material of the positive electrode material are the same as in Example 1).

[0057] Step 5: Assemble the zinc-iodine full battery using the prepared positive electrode material.

[0058] Comparative Example 1 Step 1: Take 5 ml of deionized water and add it to a clean beaker. Weigh 0.815 g of N,N-dihydroxyethylglycine and 3.229 g of zinc sulfate, add them to the water, and stir until it becomes clear.

[0059] Step 2: Add deionized water to the solution in step 1 to make it 10 ml and sonicate until it is homogeneous.

[0060] Step 3: Assemble the zinc-zinc symmetrical battery with the prepared electrolyte.

[0061] Step 4: Prepare a composite electrode material of Ketjen black and PVDF, accurately control the mass ratio to 8:2, and use 16 mg of Ketjen black. Evenly disperse it in 90 μl of NMP solution and apply it on a carbon cloth current collector. After vacuum drying at 80°C for 8 hours, add 10 μl of a mixed solution of 1M potassium iodide and 0.1M iodine to obtain a positive electrode material.

[0062] Step 5: Assemble the zinc-iodine full battery using the prepared positive electrode material. Figure 1 The zinc-zinc symmetrical battery assembled with the methyltriethylammonium chloride electrolyte prepared in Example 1. From the figure, we can see that the battery operates from a small current density of 0.5 mA / cm 2 Slowly and gradually increase to 10 mA / cm 2 The current density is then reduced to 0.5 mA / cm 2 The whole process showed good reversibility and stability.

[0063] Figure 2 In the four-electron zinc-iodine full cell assembled with the methyltriethylammonium chloride electrolyte prepared in Example 1, it can be observed that as the operating conditions of the full cell gradually increase from 0.5C to 10C and then return to 0.5C, the methyltriethylammonium chloride electrolyte exhibits good reversibility while maintaining high capacity.

[0064] Figure 3 This is the charge and discharge curve of the 2C four-electron zinc-iodine full battery assembled with the methyltriethylammonium chloride electrolyte prepared in Example 1. As can be seen from the figure, the four-electron zinc-iodine battery containing the methyltriethylammonium chloride electrolyte exhibits good coulombic efficiency.

[0065] Figure 4 This is a zinc-zinc symmetrical battery assembled with the betaine hydrochloride electrolyte prepared in Example 2. From the figure, we can see that the battery operates from a small current density of 0.5 mA / cm 2 Slowly and gradually increase to 10 mA / cm 2 The current density is then reduced to 0.5 mA / cm 2The whole process showed good reversibility and stability.

[0066] Figure 5 In the four-electron zinc-iodine full cell assembled with the betaine hydrochloride electrolyte prepared in Example 2, it can be observed that when the operating conditions of the full cell gradually increase from 0.5C to 10C and then return to 0.5C, although the coulombic efficiency of the betaine hydrochloride electrolyte is not stable at the beginning, it can show good reversibility while maintaining high capacity as the number of cycles increases.

[0067] Figure 6 This is the charge and discharge curve of the 2C four-electron zinc-iodine full battery assembled with the betaine hydrochloride electrolyte prepared in Example 2. As can be seen from the figure, the four-electron zinc-iodine battery containing the betaine hydrochloride electrolyte exhibits good coulombic efficiency.

[0068] Figure 7 The zinc-zinc symmetrical battery assembled with the triethylamine hydrobromide electrolyte prepared in Example 3. From the figure, we can see that the battery operates from a small current density of 0.5 mA / cm 2 Slowly and gradually increase to 10 mA / cm 2 The current density is then reduced to 0.5 mA / cm 2 The whole process showed good reversibility and stability.

[0069] Figure 8 In the four-electron zinc-iodine full cell assembled with the triethylamine hydrobromide electrolyte prepared in Example 3, it can be observed that when the operating conditions of the full cell gradually increase from 0.5C to 10C and then return to 0.5C, the coulombic efficiency of the betaine hydrochloride electrolyte is not high, but it still has a high capacity as the cycle proceeds.

[0070] Fig. 9 The charge and discharge curve of the 2C four-electron zinc-iodine full battery assembled with the triethylamine hydrobromide electrolyte prepared in Example 3. As can be seen from the figure, the four-electron zinc-iodine battery containing the triethylamine hydrobromide electrolyte exhibits the characteristics of high capacity.

[0071] Fig.10 This is the charge and discharge curve of a 2C zinc-iodine full battery assembled with the electrolyte prepared in Comparative Example 1. As can be seen from the figure, when any of the additives selected from methyltriethylammonium chloride, betaine hydrochloride, and triethylamine hydrobromide are not added, the four-electron reaction mechanism cannot be stimulated, so the battery capacity is low.

[0072] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.

[0073] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0074] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. An electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery, characterized in that: The electrolyte comprises N,N-dihydroxyethylglycine, zinc sulfate, additives and water; In the electrolyte, the concentration of N,N-dihydroxyethylglycine is 0.5±0.2 mol / L; The molar ratio of the additive to the zinc sulfate is 1:3; The additive includes any one of methyltriethylammonium chloride, betaine hydrochloride and triethylamine hydrobromide.

2. The electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery according to claim 1, characterized in that: In the electrolyte, the concentration of zinc sulfate is 2±0.5 mol / L; In the electrolyte, the concentration of N,N-dihydroxyethylglycine is 0.5 mol / L.

3. A method for preparing an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery as claimed in claim 1 or 2, characterized in that: The preparation method comprises: N,N-dihydroxyethylglycine, additives and zinc sulfate are dissolved in water and then subjected to ultrasonic treatment to obtain an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery.

4. Use of an electrolyte for improving the interfacial stability of a four-electron aqueous zinc-iodine battery as claimed in claim 1 or 2 in the preparation of an aqueous zinc-iodine battery.

5. An aqueous zinc-iodine battery, characterized in that: The aqueous zinc-iodine battery contains the electrolyte for improving the interface stability of the four-electron aqueous zinc-iodine battery according to claim 1 or 2.

6. A high-capacity aqueous zinc-iodine battery, characterized in that: The aqueous zinc-iodine battery uses an iodine composite material as a positive electrode, metal zinc as a negative electrode, a glass fiber membrane as a separator, and an electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery according to claim 1 or 2 as an electrolyte.

7. A high-capacity aqueous zinc-iodine battery according to claim 6, characterized in that: The positive electrode is prepared by the following method: Conductive carbon and polyvinylidene fluoride (PVDF) are co-dispersed in NMP to obtain a slurry; Dissolving potassium iodide and elemental iodine in water to obtain an iodine source solution; The slurry is coated on a current collector, and after vacuum drying, the iodine source solution is added dropwise to obtain a positive electrode.

8. A high-capacity aqueous zinc-iodine battery according to claim 7, characterized in that: The mass ratio of the conductive carbon to the polyvinylidene fluoride is 8:2; The molar ratio of the potassium iodide to the iodine element is 10:1, and the concentration of the potassium iodide in the iodine source solution is 1 mol / L; The mass ratio of the conductive carbon to the iodine element is 1:1.

2.

9. A zinc-zinc symmetrical battery, characterized in that: The zinc-zinc symmetrical battery uses zinc foil as the positive and negative electrodes of the battery, a glass fiber membrane as a separator, and an electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery as claimed in claim 1 or 2 as an electrolyte.

10. A zinc-copper asymmetric battery, characterized in that: The zinc-copper asymmetric battery uses zinc foil as the negative electrode, copper foil as the positive electrode, a glass fiber membrane as the separator, and an electrolyte for improving the interface stability of a four-electron aqueous zinc-iodine battery as claimed in claim 1 or 2 as the electrolyte.

Citation Information

Patent Citations

  • Battery and preparation method of iodine electrode material and electrolyte

    CN117039207A

  • Electrolyte for improving cycle performance of battery and aqueous zinc ion battery

    CN117059911A

  • Preparation method and application of high-performance aqueous alkaline reversible high-voltage zinc ion battery electrolyte

    CN117558999A

  • Electrolyte additive based on pyrrole nitrogen chemistry, application of electrolyte additive and aqueous zinc-iodine battery

    CN119029341A

  • High energy density vanadium electrolyte solutions, methods of preparation thereof and all-vanadium redox cells and batteries containing high energy vanadium electrolyte solutions

    US20010028977A1

Cited By

  • Positive electrode additive and electrolyte for high-stability two-electron aqueous zinc-iodine battery

    CN121507139A

  • S, n co-doped carbon material for positive electrode of four-electron zinc-iodine battery and preparation method thereof

    CN122781869A

  • S, n co-doped carbon material for positive electrode of four-electron zinc-iodine battery and preparation method thereof

    CN122781869B